Development of a self‐efficacy questionnaire, 'Insulin Therapy Self‐efficacy Scale (ITSS)', for insulin users in Japanese: The Self‐Efficacy‐Q study. Issue 2 (24th September 2018) - Nakaue, Junko; Koizumi, Miyuki; Nakajima, Hiroki; Okada, Sadanori; Mohri, Takako; Akai, Yasuhiro; Furuya, Miyuki; Hayashino, Yasuaki; Sato, Yasunori; Ishii, Hitoshi
Abstract: Aims/Introduction: Although patient self‐efficacy is known to affect adherence to therapy, no available tool measures self‐efficacy of insulin therapy administration while addressing the entire therapeutic process and management. In light of this, we developed the 'Insulin Therapy Self‐efficacy Scale (ITSS).' Materials and Methods: Development of the ITSS involved three phases: (i) item generation and creation of a questionnaire draft; (ii) testing and correcting the items through interviews with patients; and (iii) a multicenter, single‐arm study to validate the questionnaire. Results: A factor analysis and Cronbach's α both confirmed good internal consistency in the patients' confidence regarding the following four factors: the insulin injection procedure, insulin titration, glycemic control and ability to cope with hypoglycemia. Reproducibility was confirmed using weighted κ statistics and intraclass correlations. Good concurrent validity was confirmed with two other questionnaires. The ITSS score was also found to correlate with several patient characteristics and clinical parameters, as well as with a better adherence to injected insulin therapy 6 months later, suggesting the predictive validity of this scale. Conclusions: The ITSS is a reliable and valid tool for assessing and quantifying patients' self‐efficacy. The ITSS estimation of self‐efficacy can predict a patient's glycemic control and future adherence to insulin therapy. These characteristics will ensure the usefulness of the ITSS in ensuring a successful therapeutic process for patients and physicians. Abstract : We developed the Insulin Therapy Self‐efficacy Scale (ITSS) to measure patient self‐efficacy with regard to the entire process of insulin therapy administration and management.